Enhanced surface emission in terahertz quantum cascade lasers using plasma layer assisted photonic crystal waveguides - Chen, Mingxi; Lin, Tsung-Tse; Wang, Li; Hirayama, Hideki; Otani, Chiko (Frontiers in Photonics, 2025)
Introduction:Surface-emitting terahertz quantum cascade lasers (THz QCLs) are highly promising for applications requiring high-quality far-field beams and controlled beam divergence. However, limited brightness and output power in conventional surface-emitting designs remain significant barriers to practical implementation. Although photonic crystal structures and distributed Bragg reflectors have been explored to enhance surface emission, intrinsic limitations in emission area scaling and brightness improvement persist. Thus, new strategies are essential to advance the performance of surface-emitting THz QCLs.Methods:This study proposes a plasma-assisted photonic crystal waveguide design to improve surface emission efficiency in THz QCLs. A three-dimensional TM-mode coupled wave theory (3D TM-mode CWT) model was developed, incorporating effective permittivity enhancement and a self-consistent iterative scheme to accurately simulate optical field distribution and interaction within the structure.Results:Simulations reveal that the introduction of a plasma layer effectively disrupts the optical field symmetry characteristic of conventional double-metal waveguides, promoting vertical emission. Through systematic optimization, a plasma layer thickness of 0.8 μm was identified as having the potential to achieve surface emission efficiencies exceeding those of conventional structures by over two orders of magnitude. This enhancement is realized without significantly increasing fabrication complexity.Discussion:The plasma-assisted photonic crystal waveguide design offers a viable pathway toward realizing high-brightness surface-emitting THz QCLs. Although challenges such as material growth control and thermal management remain, the substantial improvement in surface emission efficiency underscores the potential of this approach for future high-performance terahertz applications.